L–Arginine/l–lysine improves emulsion stability of chicken sausage by increasing electrostatic repulsion of emulsion droplet and decreasing the interfacial tension of soybean oil-water. (April 2019) - Zhu, Xiaoxu; Li, Linxian; Li, Shiyi; Ning, Cheng; Zhou, Cunliu
Abstract: The effects ofl –arginine (Arg) andl –lysine (Lys) on the emulsifying properties of the salt-soluble meat proteins (SSMPs)–soybean oil emulsion (SSOE) and soybean oil–water emulsion (SWE) were evaluated to ascertain their roles in improving the emulsion stability of sausage. The results indicated that Arg/Lys addition or increasing pH increased the emulsifying activity/stability index and the absolute ζ–potential of emulsion droplets but decreased the creaming index, apparent viscosity, and mean particle size of SSOE. Amino acid analysis showed that Arg/Lys accumulated at the interface of the emulsion droplets. Arg/Lys also decreased the surface tension of SWE at 0.002% but increased the stability of SWE at 0.1%– 0.3%. In summary, Arg/Lys improved the stability of emulsified sausage by increasing the electrostatic repulsion of emulsion droplets and decreasing the interfacial tension of soybean oil-water. Graphical abstract: Highlights: Arginine/Lysine enhanced the emulsion activity/stability index of emulsion. Arginine/Lysine decreased the creaming index of emulsion. Arginine/Lysine increased the absolute potential of emulsion droplet. Arginine/Lysine molecules were accumulated at the interface of emulsion droplets. The interfacial tension of O/W decreased with the addition of Arginine/Lysine.